Prediction value of 18F-FDG PET/CT intratumor metabolic heterogeneity parameters for recurrence after radical surgery of stage II/III colorectal cancer - Liu, Xin; Zhang, Yi-Fan; Shi, Qin; Yang, Yi; Yao, Ben-Hu; Wang, Shi-Cun; Geng, Guang-Yong (Frontiers in Oncology, 2022)
Purpose: We explored the predictive effect of intratumor metabolic heterogeneity indices extracted from 18F-FDG PET/CT on recurrence in stage II/III colorectal cancer after radical surgery. Methods: An amount of 140 stage II/III colorectal cancer patients who received preoperative 18F-FDG PET/CT and radical resection were enrolled. 18F-FDG traditional parameters including the maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) under different thresholds, heterogeneity indices including the coefficient of variation with SUV 2.5 as a threshold (CV2.5), CV40%, heterogeneity index-1 (HI-1) calculated by fixed thresholds method, and HI-2 calculated by percentage thresholds method, and clinicopathological information were collected. We concluded relationships between these data and patients' disease-free survival (DFS). Results: Regional lymph nodes status (P<0.001), nerve invasion (P=0.036), tumor thrombus (P=0.005), HI-1 (P=0.010) exhibited significant differences between relapse and non-relapse groups, while SUVmax, MTV2.5, MTV40%, TLG2.5, TLG40%, CV2.5, CV40%, HI-2, and other clinicopathological factors had no differences between relapse and non-relapse groups. Multivariate analysis demonstrated HI-1 (HR=1.02, 1.00-1.04, P=0.038), regional lymph nodes metastasis (HR=2.95, 1.37-6.38, P=0.006), and tumor thrombus status (HR=2.37, 1.13-4.99, P=0.022) were independent factors significantly related to DFS. Conclusion: HI-1, tumor thrombus status, regional lymph nodes status could predict the recurrence of stage II/III colorectal cancer after radical resection，and had an advantage over other 18F-FDG PET/CT conventional parameters and heterogeneity indices.